Phase Transformation of TiO2 Thin Films in Function Bias Voltage - Franco Arias, Lina Maria (2015)
Titanium dioxide thin films have been deposited on silicon (100) and 316L stainless steel substrates by cathodic arc deposition in oxygen atmosphere with a titanium cathode. The process was run at room temperature and at 300 °C, biasing the substrate with pulsed voltage (up to ?10 kV) and DC voltage (up to ?120 V). The crystalline structure was studied by Raman spectroscopy and X-ray diffraction. At room temperature, the films were obtained with an amorphous base with small isolated crystals of rutile and anatase. At 300 °C, with DC bias, samples grew crystalline with the presence of both anatase and rutile.